2009
DOI: 10.1038/ejhg.2009.114
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive SNP-chip for retinitis pigmentosa-Leber congenital amaurosis diagnosis: new mutations and detection of mutational founder effects

Abstract: Fast and efficient high-throughput techniques are essential for the molecular diagnosis of highly heterogeneous hereditary diseases, such as retinitis pigmentosa (RP). We had previously approached RP genetic testing by devising a chip based on co-segregation analysis for the autosomal recessive forms. In this study, we aimed to design a diagnostic tool for all the known genes (40 up to now) responsible for the autosomal dominant and recessive RP and Leber congenital amaurosis (LCA). This new chip analyzes 240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Overall, mutations in splicing factor genes are the second most common cause of adRP [2]. We identified heterozygous mutations in adRP splicing genes ( SNRNP200 , PRPF8 , PRPF31 ) in 17 probands (Table 1) [2,26,28,4749]. …”
Section: Sequence and Copy Number Variationsmentioning
confidence: 99%
“…Overall, mutations in splicing factor genes are the second most common cause of adRP [2]. We identified heterozygous mutations in adRP splicing genes ( SNRNP200 , PRPF8 , PRPF31 ) in 17 probands (Table 1) [2,26,28,4749]. …”
Section: Sequence and Copy Number Variationsmentioning
confidence: 99%
“…This genotyping kit, TaqMan ® PCR Master Mix, No AmpErase ® UNG and approximately 5 ng genomic DNA were employed in a final volume of 5 L. A 7300 Real-Time PCR System was used for amplification, and the first step of the thermocycle was initial denaturation and activation at 95 for 10 minutes, followed by 40 cycles of 95 for 15 seconds and 60 for 1 minute. SNP kits for C_26207636_10 (rs4240897), C_1267235_20 (rs1474868), C_11461995_10 (rs2336384), C_8861262_10 ( r s 8 7 3 4 5 8 ) , C _ 1 1 4 6 1 9 9 6 _ 2 0 ( r s 8 7 3 4 5 7 ) , C_1267226_10 (rs4846085) were used and the genotypes detected following the instructions supplied by Applied Biosystems 12) .…”
Section: Detection Of Genotypementioning
confidence: 99%
“…The resequencing chip theoretically circumvents this limitation, but the prerequisite step of amplifying all known RD genes represents a major challenge (Booij et al 2011). We and others have shown that the autozygome approach can be very effective in guiding the mutation analysis (Aldahmesh et al 2009;Pomares et al 2010). Interestingly, this approach was also used successfully in populations where consanguinity is uncommon (Hildebrandt et al 2009;Collin et al 2011;Hagiwara et al 2011;Schuurs-Hoeijmakers et al 2011).…”
Section: Autozygome/exome Analysis In Retinal Dystrophymentioning
confidence: 99%